Addressing Unmet Basic Needs to Improve Colposcopy Adherence Among Women With Abnormal Cervical Cancer Screening. Issue 2 (April 2021) - Kuroki, Lindsay; Massad, L. Stewart; Martin, Anne; Liu, Jingxia; Brown, Dominique; Leon, Andrea; Groesch, Kathleen; Wilson, Teresa; Zeino, Yahia; Diaz-Sylvester, Paula; Delfino, Kristin; Hyon, Katherine; et al.
Abstract : Objectives: The aims of the study were to identify unmet basic needs (BNs) among women referred to colposcopy, to assess patient acceptability/satisfaction with assistance from a navigator to address unmet BNs, and to estimate adherence to colposcopy. Methods: Women were recruited between September 2017 and January 2019 from 2 academic colposcopy centers, one serving a rural and one an urban area. Basic needs were assessed by phone before colposcopy appointments and considered unmet if unlikely to resolve in 1 month. Colposcopy adherence prestudy and poststudy implementation was abstracted over 4–6 months from administrative records. After a lead-in phase of 25 patients at each site, a BN navigator was offered to new participants with 1 or more unmet BNs. Primary outcome was adherence to initial appointment. Results: Among 100 women, 59% had 1 or more unmet BNs, with similar prevalence between urban and rural sites. Adherence to initial colposcopy was 83% overall, 72% at the rural clinic, and 94% at the urban clinic ( p = .006). These adherence rates were improved from 4 months before study launch (30/59 [51%] rural clinic and 68/137 [50%] urban clinic). Although acceptability of BN navigation was greater than 96% and women felt that it helped them get to their colposcopy visit, having a navigator was not associated with adherence. Women reporting no unmet BNs had the lowest adherence compared with women with 1 or more unmet BNs, regardless of navigator assistance ( p = .03). Conclusions: Disadvantaged women who need colposcopy have unmet BNs and value navigator assistance for initial appointments. However, when appointment scheduling includes telephone reminders and inquiring about BNs, a navigator may not add value. Abstract : Supplemental digital content is available in the text.